Board leadership structure and human capital disclosure: Role of independent directors - Francisca Tejedo-Romero; Angel Tejada Ponce; Yolanda Ramírez; María Del Mar López Pérez (European Research on Management and Business Economics (ERMBE), 2023)
This study investigates board characteristics, including board leadership structure, which explain the human capital disclosure (HCD) provided by companies. It uses a self-constructed disclosure index to quantify the level of human capital information using content analysis. Generalized method of moment is employed to estimate a dynamic model of the relationship between HCD and the characteristics of boards of directors. The results show that companies are adapting to the new European Union (EU) Regulation Directive 2014/95/EU by increasing their HCD. There has been a change in the topics disclosed by companies that signal a commitment to social responsibility toward their employees and stakeholders. The level of HCD is significantly associated with board leadership structure, and independent directors play a moderating role when a chief executive officer (CEO) duality exists. Additionally, factors such as gender diversity, board size, board activity, company size and age, and the EU Directive approved in 2014 are all associated with HCD. This study enriches the debate on the role of independent directors in HCD because they can exercise a moderating role when CEO duality is present.
Keywords: M14; M19; M41; G39; 650; Human capital disclosure; Content analysis; Board; Independent directors; Corporate Reports